Pemanfaatan Lahan Pekarangan Rumah untuk Budidaya Sayuran Hidroponik di Kelurahan Potulando Kecamatan Ende Tengah Kabupaten Ende - Jariyah, Ainun; Wae, Veronika Praja Sinta Mbia; Gago, Jumilah; Abdullah, Adi Neneng (LPPM Universitas Flores, 2022)
Topographically, Potulando Village is located in the highlands and lowlands and is located in the center of Ende City. The Potulando Village area is a mixed area, namely economic and residential areas. As one of the urban villages located in the middle of the city, the residential area is included in a densely populated area. Narrow yards are left unproductive and unproductive. Home yard land can be used as an effort to meet family food availability through intensification of cultivation of various types of agricultural crops. One of the farming techniques that can be applied to a narrow area is hydroponics. Hydroponics is a method of farming by utilizing water without using soil as a growing medium. The method used in Community Service activities in the group of PKK cadres in the village of Potulando with several methods, namely 1) socialization of narrow land use, good farming methods, and fertilization methods, and 2) training and practice of making hydroponic plants. From the results of this activity, it is expected to increase the knowledge and skills of the community in the use of home yards for farming using hydroponic techniques.